Nanogrids and Picogrids and Their Integration with Electric Vehicles - Chattopadhyay, Surajit (IET energy engineering series ;, 2022)
This practical reference covers the key concepts and technologies of nano- and picogrids in conjunction with connected generation, EV charging, IoT and cloud computing, and power quality and protection issues. Case studies help provide a full understanding of the concepts explored